Integrating AI Tools in Language Learning: A Pathway to English Proficiency for Business, Computer Science, and Accounting Students in Applied Colleges - Kamal, Mohammed Shahid (Technium Education and Humanities, 2025)
In today's interconnected world, English proficiency has become essential for students in applied disciplines such as Business, Computer Science, and Accounting, where global communication and collaboration are the norm. This study examines how technological innovations can be leveraged in language education to enhance English proficiency among undergraduate students in these fields. A quasi-experimental mixed-methods approach was employed, comparing outcomes between a traditional instruction group and a group using technology-enhanced learning tools—including AI-powered writing assistants, gamified language applications, and speech recognition software. The results indicate that students who engaged with these digital tools showed significantly greater improvements in writing, speaking, and overall confidence in English communication. At the same time, the study highlights challenges related to unequal access to technology, difficulties in integrating new tools into curricula, and resistance to adopting unfamiliar platforms. Practical strategies to overcome these barriers are discussed. Overall, the findings emphasize technology’s role as a bridge to stronger language skills and propose recommendations for thoughtfully incorporating digital tools into English language curricula across applied disciplines.